Android-Based Information And Internet Dictionary Applications Using The Horspool Algorithm - M. Husni Rifqo; Widia Ayuni Kartika (Jurnal Komputer, Informasi dan Teknologi (JKOMITEK), 2022)
Currently, many technical term dictionaries that are currently circulating are still in book form, making it difficult for users, especially students, because they have to manually search for the meanings and terms of informatics and the internet. One of the algorithms commonly used in the searching process is the Horspool algorithm. Horspool algorithm is a text matching process. Text matching will run efficiently if you have a table to determine how long the character is shifted if an inconsistency is detected in the jth character of the pattern. So it is hoped that the search process can be made in the application of the informatics and internet term dictionary. By using the Horspool algorithm, word matching will be carried out from the beginning of the text or from left to right so that the number and position of the searched term will determine the duration of the search.